2020
DOI: 10.3390/children7100180
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Monitor Oxygenation during the Management of PPHN? Alveolar, Arterial, Mixed Venous Oxygen Tension or Peripheral Saturation?

Abstract: Oxygen is a pulmonary vasodilator and plays an important role in mediating circulatory transition from fetal to postnatal period. Oxygen tension (PO2) in the alveolus (PAO2) and pulmonary artery (PaO2) are the main factors that influence hypoxic pulmonary vasoconstriction (HPV). Inability to achieve adequate pulmonary vasodilation at birth leads to persistent pulmonary hypertension of the newborn (PPHN). Supplemental oxygen therapy is the mainstay of PPHN management. However, optimal monitoring and targeting o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…With 100% supplemental O 2 , the average arterial O 2 tension (PaO 2 ) was <100 mm Hg in the first 10 min. Perinatal depression, acidosis, and RDS can hamper the decrease in pulmonary vascular resistance and an improvement in pulmonary blood flow [ 8 , 15 , 16 ]. In our study, the use of 30% oxygen was associated with lower peak pulmonary blood flow than the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…With 100% supplemental O 2 , the average arterial O 2 tension (PaO 2 ) was <100 mm Hg in the first 10 min. Perinatal depression, acidosis, and RDS can hamper the decrease in pulmonary vascular resistance and an improvement in pulmonary blood flow [ 8 , 15 , 16 ]. In our study, the use of 30% oxygen was associated with lower peak pulmonary blood flow than the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The release of inflammatory mediators induces vasoconstriction, whereas acidosis further exacerbates increases in PVR 26 . Additionally, regional hypoxic pulmonary vasoconstriction not only diverts blood away from underventilated alveoli but also contributes to the overall increase in PVR and RV afterload effects 27 . Therefore, optimization of lung recruitment is of paramount importance before administration of selective pulmonary vasodilators like iNO to ensure efficacious delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Asphyxia with combined respiratory and metabolic acidosis shifts the hemoglobin-oxygen dissociation curve leading to lower SpO 2 for a given PaO 2 . We speculate that with better ventilation (lower PaCO 2 ) and higher pH in the DCCV group, SpO 2 values were higher despite lower PaO 2 levels in DCCV compared to ECCV [ 26 ]. By 5 min, the highest PaO 2 in DCCV was 38 ± 9 mmHg compared to ECCV, where it was 96 ± 65 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Although the change point (PaO 2 value) for pulmonary vascular transition in an asphyxiated preterm neonate/model remains unknown, we have previously shown that in a non-asphyxiated preterm model, a PaO 2 of 31 ± 0.7 mmHg led to a drop in PVR [ 36 ]. In our study, we speculate that despite the lower PaO 2 observed in the arterial blood, higher alveolar PAO 2 helped overcome hypoxic pulmonary vasoconstriction and an improvement in pulmonary vascular transition in the DCCV group [ 26 ]. Custer et al have shown that alveolar hypoxia could worsen hypoxic pulmonary vasoconstriction leading to a redistribution of pulmonary blood flow in a newborn ovine model [ 37 ].…”
Section: Discussionmentioning
confidence: 99%